PENGEMBANGAN BAHAN AJAR BERBANTUAN AMRITA OLABS PADA MATERI GELOMBANG BUNYI - Arsel Bungkuran; Heindrich Taunaumang; Alfrits Komansilan (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2021)
The study was carried out with the goal of producing teaching products with the aid of Amrita olabs on sound wave materials for the 11th grade in physics. The study was conducted at 11th SMA Negeri 1 Tondano science class, which held 33 students. In this study only 22 of the 33 trainees participated in the study. Amrita olabs is the latest innovation for simulations of virtual laboratory experiments. Amrita olabs can be used not only in labtop but also in android/iphone phones. The research method used was research and development (R&D) with model 4D. Data retrieval involves validating the learning tools of Amrita olabs using angkets. Based on the results of improved response analysis after using the teaching material Amrita olabs is obtained that the teaching material with Amrita olabs is said to be good according to the avarage percentage of learners’ responses. The effectiveness of using an Amrita olabs based on gain value is gained 54,7% by medium category. Analysis of the results of the study suggests that the teaching material provided by Amrita olabs is worthy of use in the study of physics and is capable of improving the physical abilities of learners.